Cardiac Biomarkers in Stroke, Alzheimer’s Disease, and Other Dementia. Are They of Use? A Brief Overview of Data from Recent Investigations - Khan, Shahzad; Kamal, Mohammad A. (CNS & Neurological Disorders - Drug Targets, 2021)
Conventionally, cardiac biomarkers are recognized as an essential tool to investigate the presence or progression of various cardiovascular diseases. However, in recent years, data from several clinical trials have successfully sorted out the utility of cardiac biomarkers in diseases that are not primarily regarded as “cardiac diseases,” especially neurological diseases. Results of freshly published trials have endorsed the use of cardiac biomarkers in various forms of stroke and dementia, including Alzheimer’s disease. Alzheimer’s disease is also one of the other CNS conditions where measuring cardiac biomarkers have been found to be useful. Cardiac biomarkers can be helpful in two ways. Firstly, to assess the secondary involvement of the heart during the progression of the primary disease. Secondly, they can be useful in the diagnosis and prognosis of the primary condition itself. In this short review, we have collected encouraging results from recent studies that show the importance of the most widely recognized cardiac biomarkers in two of the most prominent neurological diseases of the current world, i.e., stroke and dementia.
Keywords: BNP